2013
DOI: 10.1371/journal.pone.0075705
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of the Stolon Cold Stress Response between the C4 Perennial Grass Species Zoysia japonica and Zoysia metrella

Abstract: Zoysiagrass, the most cold-tolerant grass among the warm-season turfgrasses, is often used as a model species for isolating cellular components related to cold stress. To understand the proteomic responses to cold stress in zoysiagrass stolons, we extracted stolon proteins from Zoysia japonica , cv. Meyer (cold-tolerant) and Z . metrella , cv. Diamond (cold-sensitive), which were grown with or without cold treatment. Approximately 700 proteins were resolved on 2-DE gels, and 70 protein spots were differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…Surprisingly, we found that cold stress induced an increase in the expression of SOD and APX in banana leaves, while the expression of another isoenzyme of SOD slightly decreased ( Table 1). The simultaneous up-and down-regulation in different isoenzymes has been detected under cold stress conditions, similar to what has been described in zoysiagrass (Zoysia japonica) stolons exposed to cold stress, and Xuan et al (2013) confirmed that functionally different APX proteins differentially respond to cold stress. Scavenging for increased ROS at low temperatures can be achieved by shifting protein expression to produce isoforms that have improved performance at low temperature.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Surprisingly, we found that cold stress induced an increase in the expression of SOD and APX in banana leaves, while the expression of another isoenzyme of SOD slightly decreased ( Table 1). The simultaneous up-and down-regulation in different isoenzymes has been detected under cold stress conditions, similar to what has been described in zoysiagrass (Zoysia japonica) stolons exposed to cold stress, and Xuan et al (2013) confirmed that functionally different APX proteins differentially respond to cold stress. Scavenging for increased ROS at low temperatures can be achieved by shifting protein expression to produce isoforms that have improved performance at low temperature.…”
Section: Discussionsupporting
confidence: 82%
“…RuBisCo activase and MCPR were found to be up-regulated in banana leaves under cold stress in this study, but the alpha subunit of Rlsbp was decreased (Table 1). Cold treatment can increase the abundance of RuBisCo and RuBisCo activase (Dumont et al, 2011;Wang et al, 2009;Xuan et al, 2013). When photosynthesis is greatly inhibited by low temperature in various crops (Allen and Ort, 2001;Jin et al, 2011), they can increase the levels of RuBisCo, RuBisCo activase, and MCPR, which are needed to compensate for decreased activities of the enzymes at low temperatures (Yamori et al, 2014).…”
Section: Involvement In Photosynthesismentioning
confidence: 99%
“…Ca 2+ acts as a secondary messenger in salt stress responses (Xuan et al, 2013 ). The cytosolic free Ca 2+ concentration ([Ca 2+ ] cyt ) changes within seconds in plants subjected to salt stress (Knight et al, 1997 ), leading to downstream signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Z. japonica has a similar ROS scavenging system to that of other plant species. Cold treatment significantly increases antioxidant enzyme levels (Xuan et al, 2013 ), which may provide protection against oxidative damage in this species (Xu et al, 2013a ). Among our DEGs, we identified 14 unigenes belonging to the ascorbate-glutathione cycle, GPX pathway, and Prx/Trx pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In a mapping group consisting of 96 zoysiagrass accessions, three SSR (simple sequence repeat) loci and one SRAP (sequence-related amplified polymorphism) locus were found to be associated with cold tolerance, and three SSR loci and two SRAP loci were found to be associated with the green period [ 11 ]. At the protein level, 70 protein spots were found differentially accumulated in stolons after a 14d-cold exposure [ 12 ]. A genome-wide investigation of the gene expression profiles would be helpful for our understanding of the cold response in plants as the gene regulation network is very complex [ 13 ].…”
Section: Introductionmentioning
confidence: 99%